PENGEMBANGAN MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS DEEP LEARNING MELALUI PENDEKATAN MULTIDISIPLINER - M. Fathun Niam (CV. ADIBA AISHA AMIRA, 2025)
This study aims to develop a deep learning-based Islamic Religious Education (IRE) learning model through a multidisciplinary approach in order to improve students' conceptual understanding, value reflection, and critical thinking skills. The deep learning approach in the context of education emphasises meaningful and reflective learning processes, rather than mere memorisation, so that religious education becomes more contextual and relevant to the dynamics of the 21st century. The research method used was qualitative with a research and development (R&D) design, involving four stages: needs analysis, conceptual model design, cross-disciplinary expert validation (religious education, educational psychology, and learning technology), and limited implementation testing in three secondary schools in West Java. Data was collected through in-depth interviews, participatory observation, and document analysis, then analysed using reflective thematic analysis. The results showed that the deep learning-based PAI learning model significantly improved students' conceptual understanding, spiritual reflection skills, and cross-disciplinary collaboration. Multidisciplinary integration (religion–science–technology) helped students relate Islamic values to current issues such as digital ethics and the environment. The use of technology and AI-based feedback also strengthened personalised learning and student engagement. This study reinforces the theories of constructive alignment, experiential learning, and technological pedagogical content knowledge (TPACK) in the context of modern Islamic education. Practically, this study recommends strengthening the digital competence of Islamic education teachers, increasing cross-disciplinary collaboration, and educational policies that encourage the integration of deep learning and technology ethics in the Islamic education curriculum. The resulting model is expected to be a reflective, adaptive, and contextual learning framework in shaping a religious, critical, and characterful generation in the digital era.